2009
DOI: 10.1037/a0017146
|View full text |Cite
|
Sign up to set email alerts
|

The effects of chronic achievement motivation and achievement primes on the activation of achievement and fun goals.

Abstract: This research examined the hypothesis that situational achievement cues can elicit achievement or fun goals depending on chronic differences in achievement motivation. In 4 studies, chronic differences in achievement motivation were measured, and achievement-denoting words were used to influence behavior. The effects of these variables were assessed on self-report inventories, task performance, task resumption following an interruption, and the pursuit of means relevant to achieving or having fun. Findings ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
54
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 79 publications
2
54
0
1
Order By: Relevance
“…In the course of the development of achievement motivation theory, he also suggested that in order to increase the need of individual progress, it can be taught to kids, adolescents and even to adults since according to Stipek's theory, the beliefs, values and the emotions related to progress are influenced by the environmental conditions and developmental changes. The findings of the research do not only validate the importance of achievement motivation in the growth and success of the societies, but also support the idea that achievement motivation can be improved through the presentation of suitable patterns and trainings (3). Attar Khameneh and Seif (4) demonstrated that training through the learning strategies of metacognitive study has a positive and significant effect on the students' motivation and academic achievement.…”
Section: Introductionsupporting
confidence: 57%
“…In the course of the development of achievement motivation theory, he also suggested that in order to increase the need of individual progress, it can be taught to kids, adolescents and even to adults since according to Stipek's theory, the beliefs, values and the emotions related to progress are influenced by the environmental conditions and developmental changes. The findings of the research do not only validate the importance of achievement motivation in the growth and success of the societies, but also support the idea that achievement motivation can be improved through the presentation of suitable patterns and trainings (3). Attar Khameneh and Seif (4) demonstrated that training through the learning strategies of metacognitive study has a positive and significant effect on the students' motivation and academic achievement.…”
Section: Introductionsupporting
confidence: 57%
“…We included a feedback condition to manipulate the achievement context of the task, as context has been shown to be an impor tant moderator of behavioral priming effects (cf. Gawronski & Cesario, 2013;Hart & Albarracin, 2009). …”
Section: Resultsmentioning
confidence: 99%
“…For example, reading words that were seman tically related to extraversion influenced social judgments in line with the primes, thus unconsciously influencing how the behavior of others was evaluated (Higgins & Bargh, 1987). For the achieve ment domain, presenting words like win, master, or achieve sub sequently leads to higher performance, as has been shown by Bargh, Gollwitzer, Lee-Chai, Bamdollar, and Trotschel (2001) and replicated by others (e.g., Engeser, 2009;Hart & Albarracin, 2009;Oikawa, 2004). According to this evidence of the prime-tobehavior effect, we should be permanently influenced by semantic primes in our daily lives.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…However, a survey of available literature shows that, surprisingly, conceptual priming has only been used to redirect the motivational drive, not to change its magnitude. Thus, subjects' motivation has been successfully shifted towards either achievement or joy (Hart & Albaraccin, 2009), either controlled or autonomous self-determination (Radel, Sarrazin, Legrain, & Gobancé, 2009), and either a promotion or a prevention focus (Steinberg & Bock, under review). This could indicate that contextual priming of the motivation level has not yet been considered by scientists or, alternatively, that it has been considered but failed to produce statistically significant, publishable effects.…”
Section: Introductionmentioning
confidence: 99%